2019
DOI: 10.1007/s10971-019-05044-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability and degradation of PEO20PPO70PEO20 triblock copolymers in mesostructured silica

Abstract: Organic-inorganic hybrid mesostructured silicas are prepared, without stirring (at pH 0.0) and with stirring (at pH 0.6) to obtain isolated and gyroidal-like attached silica grains with incorporated triblock P123 poly (ethylene oxide)-poly (propylene oxide)-poly (ethylene oxide) copolymers. Selected hybrids are submitted to various thermal and aging treatments for studying hydrolysis and oxidation of PEO and PPO chains. Two complementary spectroscopic techniques are used. Near-Infrared (NIR) with measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Top view respectively. Our assignment is in agreement with literature data [26]. A dramatic increase in resolution accompanies the increase of copolymer concentration, thus translating the effect of mesostructuration.…”
Section: Side Viewsupporting
confidence: 92%
“…Top view respectively. Our assignment is in agreement with literature data [26]. A dramatic increase in resolution accompanies the increase of copolymer concentration, thus translating the effect of mesostructuration.…”
Section: Side Viewsupporting
confidence: 92%
“…This broadening can indicate the presence of several conformations of PEO units or a decrease in mobility. 58 Moreover, an additional resonance, barely observable on the 13 C MAS NMR spectrum, is clearly detected at 65.7 ppm thanks to the CPMAS NMR experiment. This resonance could correspond either to propanol or to propoxy groups coming from zirconium n-propoxide (Zr-Opr) that was not fully hydrolyzed during the synthesis, or to a mixture of both.…”
Section: Characterization Of the Hybrid Mesophase And Efficiency Of Smentioning
confidence: 95%
“…4A and B) are slightly broadened except the resonance assigned to the CH 2 of PEO species that is drastically broadened by the water removal as already reported in the literature. 58 Indeed, dehydration of PEO moieties obviously reduces their mobility. This again suggests low interaction with the zirconia walls, by comparison with the observation of Dragoi et al 58 who reported that a simple dehydration treatment at 70 C during 26 hours was not sufficient to retract PEO chains from inside amorphous silica walls.…”
Section: Characterization Of the Hybrid Mesophase And Efficiency Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…This method was employed for the synthesis of Cu/SBA-15 materials, enabling a good dispersion of copper even at high loadings. 21,22 Yin et al suggested an improved method to use the P123-contained SBA-15 combined with solidstate impregnation methods to avoid the extra step of partial removal of P123, which was applied to the synthesis of CuO/SBA-15 for thiophene capture, 23,24 CeO2/SBA-15 for sulphur capture, 25,26 Pt/SBA-15 for hydrogen storage, 27 Co/SBA-15 for the oxidation of organic pollutants, 28 and Fe/SBA-15 for phenol degradation. 29 Also composite catalysts, i.e., Ag-CeO2/SBA-15, were prepared by using P123-contained SBA-15, showing good dispersion and catalytic performance for roomtemperature reduction of 4-nitrophenol.…”
Section: Introductionmentioning
confidence: 99%